Optimization Planning of Cartridge Replacement Time at Water Treatment Plant of PT Surabaya Industrial Estate Rungkut (Sier)) - Putri, Imro'atus (Jurnal Lingkungan Kebumian Indonesia, 2025)
The escalating demand for clean water requires high efficiency in its treatment and PT. Surabaya Industrial Estate Rungkut (SIER) employs a recycling process that utilizes ultrafiltration and reverse osmosis to purify its Industrial Processed Wastewater effluent to provide clean water for its tenants. However, the high frequency of cartridge replacement has resulted in increased operational costs. This is due to unoptimal pre-treatment and inadequate maintenance procedures. The objectives of this study are to design an optimized cartridge replacement, implement water quality compliance according to Ministry of Health Regulation No. 2 of 2023 and OHS standard, and implement professional engineering ethics. The results suggest that there is a necessity to improve the pretreatment process to reduce specific contaminants (Fe, Mn, Al, oil and grease, adjust the doses of coagulant and flocculant based on the characteristics of the influent, employ an agitator for homogeneous mixing and flocculation, monitor critical parameters regularly, and schedule maintenance based on actual conditions. This approach is intended to extend the lifespan of cartridges and reduce operational costs without compromising water quality. The optimization plan is expected to achieve sustainable operational efficiency, ensure regulatory compliance and workplace safety, and support the development of engineering competencies in the operations.